A BRIEF REVIEW OF SIYASAH SYAR’IYYAH’S PRINCIPLES ON COMMUNITY PARTICIPATION IN THE FORMULATION OF LOCAL REGULATION NUMBER 2 OF 2022 CONCERNING ACCOUNTABILITY FOR THE IMPLEMENTATION OF THE REGIONAL BUDGET IN SOPPENG REGENCY - Ahmad Faisal Faisal; Andi Tenripadang; Kiljamilawati; Andi Muh. Taqiyuddin BN (LPPM Universitas Bina Insan, 2026)
This study aims to analyze the role of community participation in the drafting of Local Regulation (Perda) Number 2 of 2022 concerning Accountability for the Implementation of the Regional Budget (APBD) in Soppeng Regency from the perspective of siyasah syar'iyyah. The objectives of this study are based on the following main issues: (1) How does community participation in the drafting of local regulations provide input at each stage of the regulation formation process? (2) How does the perspective of siyasah syar'iyyah view community participation in the drafting of regional regulations?This study uses a qualitative method with a juridical-sociological approach. Data collection was carried out through document analysis, interviews with policy makers, and observation of the legislative process in Soppeng Regency. The data obtained was analyzed descriptively and analytically to describe community involvement in the local regulation drafting process and explore its involvement with the principles of siyasah syar'iyyahThe results of this study show that, overall, although community participation has been implemented, there is a need for improvement in the existing mechanisms. Local governments and regional representative councils need to increase socialization, expand access to information, and create more inclusive and representative spaces for participation. These steps will make community participation more substantial and have a significant impact on the quality of the local regulations draft